Прагматична спрямованість англійських емотивних висловлень позитивної оцінки в комунікативній ситуації поздоровлення - Мудрик, Лариса Валентинівна; Mudryk, L.V. (Волин. нац. ун-т ім. Лесі Українки, 2010)
Стаття присвячена вивченню прагматичних та семантичних особливостей англійських емотивних висловлень позитивної оцінки в комунікативній ситуації поздоровлення. Виявляється іллокутивний потенціал позитивно-оцінного висловлення та виділяються засоби вербалізації позитивної оцінки адресата в ситуації поздоровлення. The article deals with the study of pragmatic and semantic peculiarities of English emotive positive-evaluative utterances in the communicative situation of congratulation. The illocutionary potential of a positive-evaluative utterance is revealed and means of verbalization of the addressee’s positive evaluation in the communicative congratulatory situation are distinguished.
Pragmatic Orientation of English Emotive Positive-Evaluative Utterances in the Communicative Situation of Congratulation.
Keywords: комунікативна ситуація поздоровлення; communicative situation of congratulation; позитивна оцінка; positive evaluation; позитивно-оцінне висловлення; positive-evaluative utterance; емотивно-оцінна лексика; emotive-evaluative lexical units; мовець; speaker; адресат; addressee; комунікативна інтенція; communicative intention; іллокутивна сила; illocutionary force